Epidemiology of acute respiratory infections among under-fives in a rural community of Trivandrum district, Kerala - Sebastian, Shaliet Rose (International Journal Of Community Medicine And Public Health, 2018)
Background: More than 2 million children die from pneumonia each year, accounting for almost 18 percent of under five deaths worldwide. Childhood ARI is a significant public health problem in India, although robust epidemiological data are not available on its incidence. In recent years, the burden posed by ARI in underdeveloped and developing countries has stimulated global concern. The objective of the study was to study the occurrence of acute respiratory infections (ARI) in children under the age of five years in Nellanad Panchayat, Trivandrum district and to study the factors associated with ARI in children under five years of age. Methods: A community based cross-sectional study was conducted among 375 children below the age of five years. Results: Occurrence of ARI was found to be 52%. A significant association was found between ARI and under-nutrition, low birth weight, poor breast feeding practices, poor parental education, exposure to passive smoking and inadequate indoor ventilation. Conclusions: The study points towards the importance of basic health promotional measures like good antenatal care, proper breast feeding practices, proper nutrition of the child and socio-economic improvement in prevention and control of ARI.